Go and stop signals for glial regeneration. (December 2017) - Hidalgo, Alicia; Logan, Ann
Highlights: The glial regenerative response to CNS injury is evolutionarily conserved. Glial proliferation and differentiation critically depend on the genes kon-tiki/NG2 and pros/prox-1 . Two positive feedback loops provide 'go-signals' that induce a rapid regenerative response. Two negative feedback loops deliver 'stop signals' that terminate the response. Injury re-activates a developmental mechanism that normally maintains structural homeostasis. Abstract : The regenerative response of ensheating glia to central nervous system (CNS) injury involves proliferation and differentiation, axonal re-enwrapment and some recovery of behaviour. Understanding this limited response could enable the enhancement of it. In Drosophila, the glial progenitor state is maintained by Notch, an activator of cell division and Prospero (Pros), a repressor. Injury provokes the activation of NFκB and up-regulation of Kon-tiki (Kon), driving cell proliferation. Homeostatic switch-off comes about as two negative feedback loops involving Pros terminate the response. Importantly, the functions of the kon and pros homologues NG2 and prox1, respectively, are conserved in mammalian NG2 glia. Controlling these genes is key for therapeutic manipulation of progenitors and stem cells to promote regeneration of the damaged CNS.